2016
DOI: 10.1210/en.2015-2040
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Transduction Pathways Mediate Thyrotropin Receptor Signaling in Preosteoblast-Like Cells

Abstract: It has been shown that the TSH receptor (TSHR) couples to a number of different signaling pathways, although the Gs-cAMP pathway has been considered primary. Here, we measured the effects of TSH on bone marker mRNA and protein expression in preosteoblast-like U2OS cells stably expressing TSHRs. We determined which signaling cascades are involved in the regulation of IL-11, osteopontin (OPN), and alkaline phosphatase (ALPL). We demonstrated that TSH-induced up-regulation of IL-11 is primarily mediated via the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…The knockdown of b-Arr 1 confirmed our previous finding that b-Arr 1-mediated signaling plays a pivotal role in TSH-induced OPN secretion (Boutin et al, 2014). Recently, we showed that multiple TSHR-activated signaling pathways lead to OPN secretion (Boutin et al, 2016). More importantly, we demonstrated that the potentiating effect of D3-bArr is solely mediated by b-Arr 1 and not by b-Arr 2 (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The knockdown of b-Arr 1 confirmed our previous finding that b-Arr 1-mediated signaling plays a pivotal role in TSH-induced OPN secretion (Boutin et al, 2014). Recently, we showed that multiple TSHR-activated signaling pathways lead to OPN secretion (Boutin et al, 2016). More importantly, we demonstrated that the potentiating effect of D3-bArr is solely mediated by b-Arr 1 and not by b-Arr 2 (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…It has been known that the TSHR can interact with members of all G protein families (Laugwitz et al, 1996), and we showed previously (Boutin et al, 2014) that TSHR activation by TSH will lead to b-Arr 1-mediated signaling. Specifically, we showed that TSHR-induced upregulation of osteoblast gene markers in U2OS-TSHR cells, like PTH effects in bone precursors (Gesty-Palmer et al, 2009), is mediated by G protein-and b-arrestinmediated pathways (Boutin et al, 2014(Boutin et al, , 2016, with TSHR acting via b-Arr 1 and PTH1R via b-Arr 2. We demonstrated that TSH-induced upregulation of interleukin 11 is primarily mediated via G s -cAMP-protein kinase A, ALPL upregulation is predominantly regulated by activation of G q/11 -phosphokinase C-ERK1/2 and OPN expression, and secretion is mediated by b-Arr 1 and G i -p38a mitogen-activated protein kinase cascades (Boutin et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although multiple coexisting mechanisms may lead to impaired physical function in patients on dialysis (e.g., older age, comorbidities, and inflammation) (43), it is plausible that myalgia, reduced muscle strength, higher oxygen requirements during physical activity, and refractory anemia ensuing from hypothyroidism may be potent yet under-recognized contributors (8,(44)(45)(46)(47)(48). Indeed, it is established that thyroid hormones have direct action in nearly every tissue, including the skeletal muscle, bone and cartilage, and the heart, and emerging data suggest TSH may have extrathyroidal effects on these end organs given the presence of TSH receptors in skeletal muscle, bone, and brain (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%